Is high-speed rail socially exclusive? An evidence-based worldwide analysis. (January 2022) - Dobruszkes, Frédéric; Chen, Chia-Lin; Moyano, Amparo; Pagliara, Francesca; Endemann, Peter
Highlights: Research on transport justice has neglected high-speed rail. The social profiles of high-speed rail passengers diverge from nationwide population. Marked inequalities relate to incomes, education and occupation. Gender and age are also differential. Greener transport modes can thus be socially exclusive. Abstract: The extent to which high-speed rail (HSR) could be socially egalitarian has been disregarded, despite evidence that upper social-occupational groups are the primary users of high-speed trains (HSTs). In this context, this review aims to fill the gap by investigating the social attributes of HSR passengers based on worldwide, available ex post data derived from surveys at both national and corridor levels. The study's results converge to conclude that HSR passengers are predominantly male, higher income, highly educated and belonging to higher social-occupational groups. Key indicators of social inequalities (i.e. income, occupational group and education) show a much sharper differentiation in HSR use than gender and age. Social inequalities arguably shape the uneven use of HSR through available income compared to HSR fares; through income compared to total expenditure on non-business travel; and through travel purposes, considering the high share of business travel aboard HSTs. Our findings highlight "greener" transport means and policies may not be socially inclusive. They also raise the issue of facilities (co-)funded by taxpayers that do not benefit the masses.